2005
DOI: 10.1007/bf03345376
|View full text |Cite
|
Sign up to set email alerts
|

Long-term potassium citrate therapy and bone mineral density in idiopathic calcium stone formers

Abstract: Several authors have described an association between idiopathic calcium (Ca) stone disease and bone mass reduction. Hypocitraturia is a frequent feature of urolithiasis, and alkaline citrate has been recommended as one of the choice treatments in this disease. Some evidence exists as to the positive effect of potassium (K) citrate therapy on bone mass. The aim of this work was the longitudinal evaluation of bone mineral density (BMD) changes in a group of Ca oxalate stone formers treated with K citrate for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…In postmenopausal women, despite no apparent acidification defect, the administration of potassium citrate at approximately the same dosage as we used induced a significant increase in urinary citrate with a parallel significant reduction in the urinary calcium and bone reabsorption markers, together with an improvement in bone mass (25). In patients with idiopathic calcium urolithiasis, treatment with potassium citrate can reverse bone loss (26,27).…”
Section: Discussionmentioning
confidence: 80%
“…In postmenopausal women, despite no apparent acidification defect, the administration of potassium citrate at approximately the same dosage as we used induced a significant increase in urinary citrate with a parallel significant reduction in the urinary calcium and bone reabsorption markers, together with an improvement in bone mass (25). In patients with idiopathic calcium urolithiasis, treatment with potassium citrate can reverse bone loss (26,27).…”
Section: Discussionmentioning
confidence: 80%
“…High-protein-fed rats supplemented with K-citrate demonstrated an increase of bone mass and bone hystomorphology compared with control animals (Zerwekh et al 2009). A prospective study carried out on 109 patients (Vescini et al 2005) affected by idiopathic kidney stone disease indicated that the increase in bone mass was related to the administration of Kcitrate for two years (bone mass density 0.451 ± 0.081 versus 0.490 ± 0.080 g/cm 2 , T-score À1.43 ± 1.02 versus À0.90 ± 1.04). The authors concluded the increased bone density was directly correlated to cessation of the demineralization process, as urinary calcium excretion rate remained unchanged.…”
Section: Effect Of Supplementation On Bonementioning
confidence: 99%
“…As an alternative, supplementation with alkalizing compounds has been suggested as a tool to limit the detrimental effect of acidosis and prevent bone loss [15]. Potassium citrate (K citrate) is a potassium salt of the citric acid that is used to increase the urinary pH, thus preventing the precipitation of solutes and the formation of kidney stones [16]. However, recent findings demonstrated that lithogenic risk factors are detectable also in postmenopausal women who exhibit osteopenia, but not urolithiasis, thus reinforcing the hypothesis that potassium citrate supplementation could have beneficial effects in preventing the bone loss progression [17].…”
Section: Introductionmentioning
confidence: 99%